Shevde, Nirupama (Rupa) interview - (:unkn) unknown (My University, 2010)
Nirupama (Rupa) Shevde is the Director of Outreach Experiences, Morgridge Institute for Research as well as WiCell Research Institute Senior Scientist and Director of Education and Outreach. She is also a UW-Madison honorary associate/fellow in Biochemistry at the College of Agricultural and Life Sciences. This interview documents her participation in the early conceptualization and development of the Wisconsin Institutes for Discovery.